Evaluating the role of critical success factors of Total quality management (TQM) implementation through SmartPLS in industrialized building projects (IBS) - Aawag Mohsen Alawag; Wesam Salah Alaloul; Hisham Mohamad; M.S. Liew; Mokhtar Awang; Abdullah O. Baarimah (Ain Shams Engineering Journal)
This study develops a model for Total Quality Management (TQM) in Malaysian Industrialized Building System (IBS) projects, examining the impact of critical success factors (CSFs) on TQM application. Within the scope of a survey carried out among construction experts, 371 valid answers were processed, which is regarded as adequate for performing Structural Equation Modeling (SEM) analysis. Through a survey among construction experts in Malaysia and subsequent PLS-SEM analysis, six CSFs were identified as significantly influencing TQM implementation in IBS projects. These factors underscore the importance of strategic focus on key areas to enhance TQM practices within the construction industry. Collectively, these CSFs account for 70.7 % of the effectiveness in implementing TQM, indicating their substantial role in the success of TQM strategies. The outcomes of this research have significant implications for the decision-making process in the construction field, particularly in the context of Malaysian Industrialized Building System (IBS) projects.